Reviews in fluorescence 2016 - Geddes, Chris D. (Springer, 2017)
Reviews in Fluorescence 2016, the tenth volume of the book serial from Springer, serves as a comprehensive collection of current trends and emerging hot topics in the field of fluorescence and closely related disciplines. It summarizes the year's progress in fluorescence and its applications, with authoritative reviews specialized enough to be attractive to professional researchers, yet also appealing to the wider audience of scientists in related disciplines of fluorescence. Reviews in Fluorescence offers an essential reference material for any research lab or company working in the fluorescence field and related areas. All academics, bench scientists, and industry professionals wishing to take advantage of the latest and greatest in the continuously emerging field of fluorescence will find it an invaluable resource.
Keywords: Fluorescence.; elektronické knihy; electronic books